2021
DOI: 10.3389/fpls.2021.712438
|View full text |Cite
|
Sign up to set email alerts
|

At-CycD2 Enhances Accumulation of Above-Ground Biomass and Recombinant Proteins in Transgenic Nicotiana benthamiana Plants

Abstract: Transient expression in Nicotiana benthamiana holds great potential for recombinant protein manufacturing due to its advantages in terms of speed and yield compared to stably transformed plants. To continue improving the quantity of recombinant proteins the plant host will need to be modified at both plant and cellular levels. In attempt to increase leaf mass fraction, we transformed N. benthamiana with the At-CycD2 gene, a positive regulator of the cell cycle. Phenotypic characterization of the T1 progeny pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 54 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…Similar increases in GFP and scFv-TM43-E10 yield were observed in N. benthamiana plants co-infiltrated with the plant-derived cell cycle regulators At-CycD2 and At-CDC27a and full TMV-based vector carrying GFP and scFv-TM43-E10 (Kopertekh and Schiemann, 2019b). Another study confirmed the positive effect of stably integrated At-CycD2 on production of GFP and scFv-TM43-E10 provided by the deconstructed TMV-based TRBO vector (Kopertekh and Reichardt, 2021).…”
Section: A B Figuresupporting
confidence: 60%
See 2 more Smart Citations
“…Similar increases in GFP and scFv-TM43-E10 yield were observed in N. benthamiana plants co-infiltrated with the plant-derived cell cycle regulators At-CycD2 and At-CDC27a and full TMV-based vector carrying GFP and scFv-TM43-E10 (Kopertekh and Schiemann, 2019b). Another study confirmed the positive effect of stably integrated At-CycD2 on production of GFP and scFv-TM43-E10 provided by the deconstructed TMV-based TRBO vector (Kopertekh and Reichardt, 2021).…”
Section: A B Figuresupporting
confidence: 60%
“…Production of recombinant proteins in the At-CDC27a transgenic and nontransgenic N. benthamiana plants Agroinfiltration was performed following the procedure described by Kopertekh and Reichardt (2021). The samples for ELISA were collected from the middle leaves at 2, 4, 6 and 10 days after infiltration (dpi).…”
Section: Phenotypic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…SPSS software (IBM Corp., Armonk, NY, USA) was used to perform the statistical analyses, and the data are represented as the mean ± SD. The Student’s t -test and one-way ANOVA were used to determine variance among the mean values [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Populus trichocarpa PtCYCB1 promoter is used to drive the expression of the CYCD gene in tobacco, which improves the cell division of vascular cambium and increases the differentiation of secondary xylem in tobacco ( Fujii et al, 2012 ). The ectopic expression of AtCYCD2 accelerates the growth and aboveground biomass accumulation rate of transgenic tobacco from the seedling stage to maturity ( Boucheron et al, 2005 ; Kopertekh and Reichardt, 2021 ). Moreover, overexpressing the CYCD3 gene into tobacco also accelerates the growth rate of leaves and changes the structure of the shoot apical meristem ( Boucheron et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%